An impact of neutrophil extracellular traps to the prothrombotic state and tumor progression in gynecological cancer patients - E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; N. D. Degtyareva; D. V. Shcherbakov; J.-C. Gris; I. Elalamy; A. D. Makatsariya (IRBIS LLC, 2023)
Introduction. One of the leading causes in the mortality pattern of cancer patients is accounted for by thrombotic complications. Recent studies have shown that neutrophil extracellular traps (NETs) are involved in the activation of coagulation, contribute to the initiation and progression of thrombosis. In addition, NET-related effect on tumor progression and metastasis has been actively studied.Aim: to evaluate NET-related procoagulant activity in gynecological cancer patients.Materials and Methods. From April 2020 to October 2022, a prospective controlled interventional non-randomized study was conducted with 120 women. The main group included 87 patients aged 32 to 72 years with malignant neoplasms of the female genital organs and mammary glands who were hospitalized for elective surgical treatment or chemotherapy: uterine body cancer (subgroup 1; n = 18), ovarian cancer (subgroup 2; n = 26), cervical cancer - adenocarcinoma of the cervical canal (subgroup 3; n = 13), breast cancer (subgroup 4; n = 30). The control group consisted of 33 healthy women aged 32 to 68 years. In all women, plasma concentrations of citrullinated histone H3 (citH3), myeloperoxidase antigen (MPO:Ag), D-dimer, and thrombin-antithrombin (TAT) complexes were evaluated.Results. The magnitude of NETosis in cancer patients, assessed by level of citH3 (2.5 ± 0.7; 1.9 ± 0.8; 2.5 ± 0.7; 0.7 ± 0.5 ng/ml in four subgroups, respectively) and MPO:Ag (29.5 ± 13.1; 12.8 ± 3.7; 22.8 ± 8.7; 6.6 ± 2.5 ng/ml in four subgroups, respectively) was significantly higher compared to women in the control group (0.3 ± 0.1 ng/ml; p = 0.0001 and 2.5 ± 0.2 ng/ml; p = 0.0001). In parallel with increased NETosis markers in accordance with the disease stage, there was an increase in the concentration of hemostasis activation markers - D-dimer (1.7 ± 0.6; 2.0 ± 0.7; 1.4 ± 0.5; 1.5 ± 0.7 µg/ml in four subgroups, respectively) and TAT complexes (729.8 ± 43.9; 794.1 ± 164.8; 636.2 ± 149.5; 699.6 ± 165.7 pg/ml in four subgroups, respectively) exceeding their level in the control group (respectively, 0.4 ± 0.1 μg/ml; p = 0.0001 and 362.3 ± 0.1 pg/ml; p = 0.0001). The maximum values of parameters occurred at later stages according to the Classification of Malignant Tumours (tumor, nodus, metastasis, TNM). A significant correlation between TAT level and the concentrations of citH3 (r = 0.586; р = 0.04) and MPO:Ag was revealed (r = 0.631; р = 0.04).Conclusion. Tumor tissue creates milieu that stimulates NETs release, which, in turn, not only contribute to the creating a procoagulant state, but also might act as one of the factors that ensure tumor progression and metastasis. The development of targeted therapies acting on NETs has a potential to affect hemostasis in cancer patients and reduce rate of tumor growth and metastasis.